Equity and law - Falcón y Tella, María José. (Leiden ; Boston : Martinus Nijhoff Publishers, 2008)
Presents a study of the different types of equity throughout history and in the different legal systems; the concept, content, limits, functions and types of equity; and, the relationship between equity and related ideas, and equity in all the branches of the legal order.
Table of Contents; Prologue; Chapter 1 Introduction; 1. The Three-Dimensional Method as the Focus of the Problem of Law in General and of Equity in Particular: Facts, Norms and Values; 2. Domain and Plan of the Project. Equity as a Multi-Faceted Topic and the Maelstrom of Interrelated Concepts. A Horizontal and Vertical Reading of this Inquiry. The Necessity of an Interdisciplinary; Chapter 2 Equity and "Time". A Dynamic Study of the Different Types of Equity Throughout History; Chapter 3 Equity in "Space". The Treatment of Equity in Different Legal Systems and Codes of Law.
Includes bibliographical references (pages 279-329) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Equity; Law -- Philosophy; LAW -- Jurisprudence; LAW -- General Practice; LAW -- Reference; LAW -- Essays; LAW -- Paralegals & Paralegalism; LAW -- Practical Guides; Equity; Law -- Philosophy; Equity; Philosophy; Philosophy of law